Liposomal amphotericin B—the future. (25th November 2022) - Hoenigl, M; Lewis, R; van de Veerdonk, F L; Verweij, P E; Cornely, O A
Abstract: Advances in medicine have led to a growing number of people with compromised or suppressed immune systems who are susceptible to invasive fungal infections. In particular, severe fungal infections are becoming increasingly common in ICUs, affecting people within and outside of traditional risk groups alike. This is exemplified by the emergence of severe viral pneumonia as a significant risk factor for invasive pulmonary aspergillosis, and the recognition of influenza-associated pulmonary aspergillosis and, more recently, COVID-19-associated pulmonary aspergillosis. The treatment landscape for haematological malignancies has changed considerably in recent years, and some recently introduced targeted agents, such as ibrutinib, are increasing the risk of invasive fungal infections. Consideration must also be given to the risk of drug–drug interactions between mould-active azoles and small-molecule kinase inhibitors. At the same time, infections caused by rare moulds and yeasts are increasing, and diagnosis continues to be challenging. There is growing concern about azole resistance among both moulds and yeasts, mandating continuous surveillance and personalized treatment strategies. It is anticipated that the epidemiology of fungal infections will continue to change and that new populations will be at risk. Early diagnosis and appropriate treatment remain the most important predictors of survival, and broad-spectrum antifungal agents will become increasingly important. Liposomal amphotericin B will remain an essential therapeutic agent in the armamentarium needed to manage future challenges, given its broad antifungal spectrum, low level of acquired resistance and limited potential for drug–drug interactions.